AZO/Ag/AZO multilayer films prepared by DC magnetron sputtering for dye-sensitized solar cell application - S. Sutthana (2018)
Ag films were deposited on Al-doped ZnO (AZO) films and coated with AZO to fabricate AZO/Ag/AZO multilayer films by DC magnetron sputtering on glass substrates without heating of glass substrates. The best multilayer films have low sheet resistance of 19.8 Ω/Sq and average transmittance values of 61% in visible region. It was found that the highest figure of merit (FTC) is 6.9 × 10-4Ω-1. For the dye-sensitized solar cell (DSSC) application, the multilayer films were used as transparent conductive electrode (multilayer films/ZnO + Eosin-Y/LiI + I2/Pt/FTO). The best DSSC based on the multilayer films showed that open circuit voltage (Voc) of 0.47 V, short circuit current density (Jsc) of 2.24 mA/cm2, fill factor (FF) of 0.58 and incident photon-to-current conversion efficiency (η) of 0.61%. It was shown that the AZO/Ag/AZO multilayer films have potential for application in DSSC. © 2009 Elsevier B.V. All rights reserved.